Cytocidal Effect of Irradiation on Gastric Cancer Cells Infected with a Recombinant Mammalian Orthoreovirus Expressing a Membrane-Targeted KillerRed - Yoshinori Shirasaka; Kentaro Yamada; Tsuyoshi Etoh; Kazuko Noguchi; Takumi Hasegawa; Katsuhiro Ogawa; Takeshi Kobayashi; Akira Nishizono; Masafumi Inomata (MDPI AG, 2024)
The outcomes of unresectable gastric cancer (GC) are unfavorable even with chemotherapy; therefore, a new treatment modality is required. The combination of an oncolytic virus and photodynamic therapy can be one of the promising modalities to overcome this. Mammalian orthoreovirus (MRV) is an oncolytic virus that has been used in clinical trials for several cancers. In this study, we developed and evaluated a recombinant MRV strain type 3 Dearing (T3D) that expresses membrane-targeting KillerRed (KRmem), a phototoxic fluorescent protein that produces cytotoxic reactive oxygen species upon light irradiation. KRmem was fused in-frame to the 3' end of the σ2 viral gene in the S2 segment using a 2A peptide linker, enabling the expression of multiple proteins from a single transcript. RNA electrophoresis, Western blotting, and immunofluorescence analyses confirmed functional insertion of KRmem into the recombinant virus. The growth activity of the recombinant virus was comparable to that of the wild-type MRV in a cultured cell line. The recombinant virus infected two GC cell lines (MKN45P and MKN7), and a significant cytocidal effect was observed in MKN45P cells infected with the recombinant virus after light irradiation. Thus, recombinant MRV-expressing KRmem has the potential to serve as a novel treatment tool for GC.